PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS FLIPBOOK DIGITAL UNTUK MENINGKATKAN KEMAMPUAN MAHASISWA UNIVERSITAS NEGERI SEMARANG - Ningrum, Setia; Maghfiroh, Anik; Ihsani, Ade; Tumangger, Mia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a digital flipbook learning media for basic facial makeup and to examine its feasibility and effectiveness in supporting learning activities. The background of this research is the limited use of interactive digital media in basic facial makeup learning, which results in students experiencing difficulties in understanding systematic makeup techniques and procedures. This study employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were students of a beauty education program. Data were collected through material expert and media expert validation sheets, student response questionnaires, and pretest–posttest instruments. The results of expert validation indicated that the digital flipbook learning media was categorized as very feasible in terms of content accuracy, presentation, and media design. Furthermore, the effectiveness test showed an improvement in students’ learning outcomes after using the digital flipbook, as indicated by the increase in posttest scores compared to pretest scores. Student responses also showed a very positive perception of the digital flipbook media in terms of attractiveness, ease of use, and usefulness in learning basic facial makeup. Based on these findings, it can be concluded that the digital flipbook learning media is feasible and effective for use in basic facial makeup learning.